The Elite - Cass, Kiera (New York, NY : HarperTeen, 2013)
"Sixteen-year-old America Singer is one of only six girls still competing in the Selection--but before she can fight to win Prince Maxon and the Illean crown, she must decide where her own heart truly lies"--
Keywords: Marriage -- Juvenile fiction; Contests -- Juvenile fiction; Social classes -- Juvenile fiction; Princes -- Juvenile fiction; Love stories; Revolutionaries -- Juvenile fiction